A fuzzy ANP–DEMATEL model on faulty behavior risks: implications for improving safety in the workplace. Issue 2 (3rd April 2022) - Karuppiah, Koppiahraj; Sankaranarayanan, Bathrinath; Ali, Syed Mithun
Abstract : The occurrence of occupational accidents and injuries has always been a major concern for industrial management. Such undesirable incidences are higher in developing countries, especially in India, than in developed countries. This research aims to identify, analyze and evaluate the faulty behavior risks (FBRs) that trigger occupational accidents and injuries. Using a data triangulation strategy, this study identified 19 FBR factors under five categories. An integrated approach comprising the fuzzy analytic network process (ANP) and the decision-making trial and evaluation laboratory (DEMATEL) method is proposed for assessing these FBRs. The five most prominent critical risk factors are the absence of continuous monitoring, defective equipment and maintenance, cognitive bias, proper signage and adverse ambient working conditions. The study postulates some implications for industrial management to mitigate occupational accidents and injuries based on the outcomes.